Auto-aggregation Properties of Probiotic Lactobacillus delbrueckii str. IAHAHI: From Genes to Function - Astghik PEPOYAN; Liana GRIGORYAN; Natalya HARUTYUNYAN; Susanna MIRZABEKYAN; Marine BALAYAN; Artak GALSTYAN; Vardan TSATURYAN; Anahit MANVELYAN (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Food Science and Technology)
The ability of bacteria to form aggregates plays an important role in controlling clinical infections and food production processes. Auto-aggregation is also important, especially in the case of probiotics, when probiotics are directed against pathogenic bacteria, promoting colonization of the intestinal mucosa with desirable bacteria. This study aims to evaluate the auto-aggregation properties of the probiotic Lactobacillus delbrueckii str.IAHAHI compared to previously studied probiotics Lacticasibacillus rhamnosus str.Vahe and Lactiplantibacillus plantarum str.ZPZ differed by their radioprotective properties. According to the received data, the auto-aggregation capacities of L. delbruetski str.IAHAHI is superior to Lcb. rhamnosus str.Vahe and Lpb. plantarum str.ZPZ after 2 hours incubation (21.97±4.099% vs.10.573±1.11% and 10.573±1.11%), while after 24 hours this strain is inferior to the other two in that feature (86.707±3.456% vs. 95.616±1.7% and 92.284±1.52%). The investigated probiotics probably differ in the expression of LysR family proteins, thioredoxin disulfide reductase, and mercury reductase. The LysR family of transcriptional regulators plays a significant role in gene expression. It might modulate bacterial membrane properties and potentially influence hydrogen peroxide production and the host’s radioprotective properties. However, it’s important to note that the specific link between hydrogen peroxide production, aggregation, and radioprotectivity is still a subject of hypothesis.